A Study on Awareness and Adoption of Large Cardamom Production Technology Among Tribal Farmers of North Sikkim - B.A.Gudade, T. N. Deka, P. Chhetri, N.K. Bhattarai, A.K. Vijayan, U. Gupta (Indian Journal of Extension Education, 2022)
..